Evaluation of a novel collagen hemostatic matrix in a porcine heart and cardiac vessel injury model - Lee, Heemoon; Lee, Jun Ho; Jeon, Chang-Seok; Ko, Jae Hyung; Park, Si-Nae; Lee, Young Tak (Journal of Thoracic Disease, 2019)
Background: Flowable hemostatic agents may be more advantageous than nonflowable hemostats, as they have capability to cover irregular wound surfaces, fill deep lesions, and easily remove excess materials with irrigation. In this study, we evaluated the hemostatic efficacy of the collagen hemostatic matrix (CHM) compared to FloSeal® via incisions in the heart and cardiac vessels in a porcine model. Methods: In each of the two female pigs, a total of two incisions were made in seven locations: right atrium (RA), right ventricle (RV), and cardiac vessels, such as the innominate vein (IV), superior vena cava (SVC), pulmonary artery (PA), coronary artery (CA), and aorta. Hemostatic agents were applied directly to the bleeding wounds. In certain location, one incision was treated with the CHM and the other with FloSeal®, and the time to hemostasis and the degree of bleeding of the two agents were assessed and compared. One week after surgery, the animals were sacrificed, and specimens were collected for histologic evaluation. Results: Bleeding from the vessels with relatively low pressure (the IV, SVC, and RA) was controlled within 1–2 minutes using both a CHM and FloSeal®. Bleeding from the vessels with high blood pressure (the RV, PA, CA, and aorta) was controlled within 3–10 minutes with the CHM. However, hemostasis in the PA and CA was not achieved with FloSeal®. Histological analysis revealed that the use of both the CHM and FloSeal® resulted in foreign body reactions of similar severity. Conclusions: The hemostatic effect and safety of the CHM may be similar to that of FloSeal®. Further clinical studies must be conducted to validate our results.